THE ROLE OF AGRICULTURAL WASTE AND FERTILIZATION LEVEL NPK ON GROWTH AND RESULTS Shallots (Allium ascalonicum L.) IN THE LAND OF THE TIDEOVERLOAD TYPE D - Hawayanti, Erni; Tri Astuti, Desi; Rizki Ananda, Dea; Ayu Sinta, Dela; Sebayang, Nico (Jurnal Pertanian, 2022)
Efforts to increase national food production include applying production technology through the use of organic fertilizers. These fertilizers can restore soil fertility. Various types of agricultural waste that can be used to make organic fertilizers are rice straw, banana weeds, water hyacinth, coconut fiber. This organic fertilizer is applied to the soil in solid form on shallot plants grown on tidal soil type D overflow, in Sukajadi village, sub-district. Talang Kelapa Banyuasin Regency. This study used a split plot design with 9 treatment combinations with 3 replications, 27 plots and 5 sample plants were obtained. The treatment factors are as follows: 1. Main Plot : fertilization rate of Compound NPK Fertilizer (N) N1 = 25% of Recommended Dose, N2 = 50% of Recommended Dose, N3 = 75% of Recommended Dose, 2. Sub-plots : Fertilizer Dose Agricultural waste (L) L1 = 5 tons/ha, L2= 0 tons/ha, L3 = 15 tons/ha. The data obtained were tested statistically using SPSS 26 software program. The variables observed in this study were plant height (cm), tuber weight per clump and tuber weight per plot. The purpose of the study was to obtain a dose of organic fertilizer from agricultural waste that could reduce the use of inorganic NPK fertilizer in tidal land, and it was hoped that it would be very useful for users as an applicative technology that was economically profitable and technologically easy to apply, for the government to overcome the problem of scarcity of fertilizers and for the community. especially farmers can increase production and standard of living. The results showed that the application of organic fertilizer from agricultural waste 15 tons/ha with 75% NPK fertilizer resulted in the best growth and yield of shallots at 11.30 tons/ha. Usaha untuk meningkatkan produksi pangan nasional antara lain dengan menerapkan teknologi produksi melalui penggunaan pupuk organik. Pupuk tersebut dapat mengembalikan kesuburan lahan.Berbagai jenis limbah pertanian yang dapat digunakan untuk membuat pupuk organik adalah Jerami Padi, Bonggol Pisang, enceng gondok, sabut kelapa. Pupuk organik ini diaplikasi ke tanah dalam bentuk padat pada tanaman bawang merah yang ditanam pada tanah pasang surut tipe luapan D, di desa Sukajadi kec. Talang Kelapa Kabupaten Banyuasin. Penelitian ini menggunakan rancangan split plot disign dengan 9 kombinasi perlakuan yang diulang sebanyak 3 ulangan didapatkan 27 petak dan 5 tanaman contoh. Adapun faktor perlakuan sebagai berikut : 1. Petak Utama : tingkat pemupukan Pupuk NPK Majemuk (N) N1 = 25 % Dari Dosis Anjuran, N2 = 50 % Dari Dosis Anjuran, N3 = 75 % Dari Dosis Anjuran, 2. Anak Petak : Dosis Pupuk Limbah pertanian (L) L1 = 5 ton/ha, L2= 0 ton/ha, L3 = 15 ton/ha. Data yang diperoleh diuji secara rganicc dengan menggunakan software program SPSS 26.Peubah yang diamati dalam penelitian ini adalah tinggi tanaman (cm), berat umbi per rumpun dan berat umbi perpetak. Tujuan penelitian untuk mendapatkan takaran pupuk organik limbah pertanian yang dapat mengurangi penggunaan pupuk NPK anorganik di lahan pasang surut, dan diharapkan sangat berguna bagi pengguna sebagai teknologi aplikatif yang secara ekonomi menguntungkan dan secara teknologi mudah diterapkan, bagi pemerintah dapat mengatasi masalah kelangkaan pupuk dan bagi masyarakat khususnya petani dapat meningkatkan produksi dan taraf hidupnya. Hasil penelitian menunjukan bahwa pemberian pupuk rganic limbah pertanian 15 ton/ha dengan pupuk NPK 75 % menghasilkan pertumbuhan dan hasil bawang merah terbaik yaitu 11,30 ton/ha.